PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP RETURN ON ASSETS PADA PERUSAHAAN SUB SEKTOR KOSMETIK - Gede Mandirta Tama; Zada Amadea Ramadhani (Jurnal Ilmiah Ekonomika & Sains, 2025)
This study aims to examine the impact of Good Corporate Governance (GCG), which consists of institutional ownership, independent commissioners, and the influence of Corporate Social Responsibility (CSR) disclosure on financial performance, as measured by Return on Assets (ROA), in the cosmetic sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2022. This study uses a quantitative method. The sampling technique applied is purposive sampling, resulting in a sample of 6 companies. The data used in this research are secondary data in the form of annual reports obtained from the official websites of the companies or the Indonesia Stock Exchange (www.idx.co.id). The analysis method employed is multiple regression analysis using SPSS version 29. The results of this study show that: (1) Institutional ownership has an effect on Return on Assets. (2) Independent commissioners have an effect on Return on Assets. (3) Corporate Social Responsibility has no effect on Return on Assets.